Compliance with the standards for prevention of ventilator-associated pneumonia by nurses in the intensive care units - Saiede Masomeh Tabaeian; Ahmadreza Yazdannik; Saeed Abbasi (Wolters Kluwer Medknow Publications, 2017)
Introduction: Ventilator-associated pneumonia (VAP) is the most common infection in the intensive care unit, and has many side effects such as increased mortality, increased length of hospital stay, and increased health costs. This study aimed to evaluate the compliance with the standards for prevention of VAP by nurses in the intensive care units. Materials and Methods: In this descriptive cross-sectional study, 120 nurses in 11 intensive care units of hospitals affiliated to Isfahan university of Medical Sciences, Iran, were assessed for 4 months from July to October 2014. The implementation of all measures for the prevention of VAP was investigated through observation and using a checklist. Results: The mean compliance with the standards for the prevention of VAP in the intensive care unit by the nurses was 56.32%; analysis of variance test showed significant difference between the hospitals (P < 0.001). Disposable ventilator circuit was performed for all patients; however, reviewing the patient readiness for separation from the ventilator was not conducted on a daily basis. Conclusions: Compliance with the standards for the prevention of VAP in the intensive care units was relatively acceptable; however, it still requires serious attention by the officials with training and sensitization of nurses in implementing preventive measures, especially through the provision of clinical guidelines and related protocols.